Manajemen Sumber Daya Manusia dalam Lembaga Pendidikan di SMA Muhammadiyyah Al Kautsar PK Kartasura - Novita Sari, Nike; Laraswati Lestari (IAIN Parepare, 2024)
This study analyzes human resource management at SMA Muhammadiyah Al Kautsar PK Kartasura to enhance the quality of education. A qualitative descriptive method with interactive analysis was employed, including observation, interviews, and documentation. The research subject was the Head of HRD, while the object covered the school’s overall HR management. Results show that teacher recruitment and selection were conducted via administrative screening, micro teaching, and interviews; regular training was provided each semester; salaries and benefits were adjusted according to experience; and dismissals were carried out in stages from SP 1 to SP 4. This HR management implementation effectively supports the improvement of teacher and staff performance and strengthens the overall effectiveness of the learning process.